Exploring the prognostic value of the novel nutritional index for in-hospital mortality in acute coronary syndrome: a sex-specific analysis - Li, Guimei; Li, Shujuan (Frontiers in Medicine, 2025)
BackgroundEmerging evidence suggests that nutritional status plays a pivotal role in determining the prognosis of patients with acute coronary syndrome (ACS). This study aimed to investigate the relationship between a novel nutritional index, Triglycerides × Total Cholesterol × Body Weight Index (TCBI), and short-term prognosis in patients with ACS.MethodsA retrospective study was conducted using data from 5,277 ACS patients admitted to intensive care units of 208 United States hospitals in the eICU Collaborative Research Database (eICU-CRD) in 2014 and 2015. Patients were divided into three groups based on TCBI tertiles: Group 1 (< 1017.97), Group 2 (1017.97–2069.02), and Group 3 (> 2069.02).ResultsMultivariate logistic regression analysis showed that after adjusting for 17 confounding variables, higher TCBI had significantly lower in-hospital mortality [Tertile 3 vs Tertile 1: OR (95% CI): 0.67 (0.48, 0.94), p = 0.019]. This relationship was significant in the male subgroup but not in the female subgroup. The association between TCBI and in-hospital mortality was more pronounced in male patients and those with blood pressure > 140 mmHg. Subgroup analysis revealed a significant interaction between sex and the predictive value of TCBI (p for interaction < 0.05).ConclusionHigher TCBI was independently associated with decreased in-hospital mortality in ACS patients, particularly in male patients. TCBI, as a novel nutritional index, may serve as a practical tool for risk stratification and personalized management of ACS patients.